Apixaban Interacts with Haemoglobin: Effects on Its Plasma Levels - Sacco, Monica; Lancellotti, Stefano; Berruti, Federico; Arcovito, Alessandro; Bellelli, Andrea; Ricciardelli, Tiziana; Autiero, Ida; Cavallo, Luigi; Oliva, Romina; De Cristofaro, Raimondo (Thrombosis and Haemostasis, 2018)
The direct oral anticoagulant apixaban (APX), a strong factor Xa inhibitor, binds also to plasma proteins, especially albumin, and minimally to α1-acid glycoprotein. Although APX can cross the red cell membrane, due to its chemical structure, and could bind to haemoglobin (Hb), no investigation was performed on this possible phenomenon that could affect the APX plasma concentration and thus its pharmacokinetics and pharmacodynamics. We addressed this issue by (1) measuring the levels of APX and haematological/biochemical parameters in 90 patients on APX therapy; (2) assessing the effect of APX on oxygen saturation curves of Hb; (3) testing the direct APX binding to Hb by fluorescence spectroscopy and a zinc-induced precipitation of Hb coupled to a reversed-phase high-performance liquid chromatography (HPLC)-based method; and (4) simulating in silico by molecular docking the APX interaction with human Hb. In a multivariable analysis, Hb was the only independent variable significantly and inversely associated in 90 patients with APX peak plasma level, at variance with patients treated with rivaroxaban (n = 86) and dabigatran (n = 34) therapy. APX causes a progressive left-shift of the oxygen dissociation curve of purified Hb solution, with a Kd ≅300 µM. Fluorescence- and HPLC-based assays concordantly showed that APX binds to Hb with a Kd ≅350 µM. Finally, docking simulations showed that APX can fit into in the central cavity of Hb. These findings support the hypothesis that APX does bind to Hb, which, due to its millimolar concentration in blood, can act as ‘buffer’ for the drug and consequently affect its free plasma level.
Keywords: anticoagulants; apixaban; erythrocytes; haemoglobin; molecular docking simulation; individualized therapy